First Complete Genome Sequence of Pepper mild mottle virus from Chili Pepper in the United States - Secrist, Kathryn (Genome Announc, 2018)
Pepper mild mottle virus (PMMoV) was first reported as a latent strain in the United States and then later reported in other countries around the world. Here, we report the first complete genome sequence of a PMMoV isolate (BL14) that was collected from chili pepper during the 2014 growing season in Oklahoma.